2013
DOI: 10.1152/ajprenal.00418.2012
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibrinogen in acute ischemic kidney injury

Abstract: Renal ischemia-reperfusion (I/R) is associated with activation of the coagulation system and accumulation of blood clotting factors in the kidney. The aim of the present study was to examine the functional impact of fibrinogen on renal inflammation, damage, and repair in the context of I/R injury. In this study, we found that I/R was associated with a significant increase in the renal deposition of circulating fibrinogen. In parallel, I/R stress induced the de novo expression of fibrinogen in tubular epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…In the mouse model, the proinflammatory profile upon catheterization was dominated by the up-regulation of IL-6, which is involved in the induction of Fg expression and potentiation of its release into the bladder lumen (26,38,(50)(51)(52). Under normal circumstances, Fg is required to aid in the healing of damaged tissue (50,52).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse model, the proinflammatory profile upon catheterization was dominated by the up-regulation of IL-6, which is involved in the induction of Fg expression and potentiation of its release into the bladder lumen (26,38,(50)(51)(52). Under normal circumstances, Fg is required to aid in the healing of damaged tissue (50,52).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies correlated Lcn2 and Fg-b expression with AKI development in mice. 28,29 Overexpression of these markers of renal injury was reduced by wild-type MSCs and EVs but not MSC-Dsh and EV-Dsh. Inefficiency of Drosha-knockdown cells and EVs in inducing renal repair was observed at not only morphologic level but also, functional levels as indicated by the persistence of elevated BUN levels.…”
Section: Discussionmentioning
confidence: 99%
“…These data collectively indicated that injured renal tubules can initiate local Fg synthesis. 29 Immunohistochemistry analysis of Fg-b in untreated AKI mice showed a strong peritubular staining for Fg and some positivity in the tubular cell cytoplasm ( Figure 7F). Tubular staining was not observed in kidneys from healthy mice and was markedly reduced in mice treated with MSC-CTRL and EV-CTRL but not MSC-Dsh and EV-Dsh ( Figure 7F).…”
Section: Effect Of Drosha Knockdown On the Expression Of Markers Of Kmentioning
confidence: 96%
See 2 more Smart Citations